Effect of Eugenia jambolana and Psidium guajava Leaf Meal Mixture Supplementation on Nutrient Utilization, Antioxidant Indices and Immune Responses in Broiler Chicks - Zargar, M. A.; Pathak, A. K.; Sharma, R. K.; Daing, M. I. (Indian Journal of Animal Nutrition, 2020)
Present study was conducted in 120 day-old unsexed broiler chicks. They were randomly distributed into 4 dietary treatments (T1, T2, T3 and T4 supplemented with Eugenia jambolana and Psidium guajava leaf meal mixture (LMM) @ 0, 2.5, 5.0 and 7.5 % of diet, respectively) of 30 birds per treatment, each having 3 replicates (10 chicks / replicate) in a complete randomized block design. Feed intake (g) in 0-3, 4-6 and 0-6 weeks were significantly (P